Towards a greater understanding of serrated flows in an Al-containing high-entropy-based alloy - Brechtl, J.; Chen, S.Y.; Xie, X.; Ren, Y.; Qiao, J.W.; Liaw, P.K.; Zinkle, S.J. (International journal of plasticity, 2019)
A serrated flow, which occurs in a material undergoing mechanical deformation, is a complex process of great engineering significance. Here statistical, dynamical, and multifractal modeling and analyses were performed on the stress-time series to characterize and model the stress-drop behavior of an Al0.5CoCrCuFeNi high-entropy alloy (HEA). Results indicate that the spatiotemporal dynamics of the serrated flow is affected by changes in the strain rate and test temperature. The sample entropy, in general, was found to be the highest in the samples tested at 500 °C. The higher complexity in the serrated flow at this temperature appeared to be associated with the stress-drop behavior that had intermediate values in terms of the maximum stress drop, the multifractality of the data set, and the histogram distributions. Moreover, the sample entropy was the lowest for the samples tested at 600 °C. The lower complexity values were associated with a wider multifractal spectrum and a less uniform and sparser distribution of the stress-drop magnitudes. In terms of the serration types, Type-C serrations were related to the lowest complexity values, widest multifractal spectra, and higher probability of exhibiting larger stress drops. Conversely, Type-A and B serrations were associated with the higher complexity, narrower spectra, and lower probability of higher stress drops. Furthermore, the body-centered-cubic (BCC) structure and the fully-ordered L12 nano-particles were found to emerge in the samples at 600 °C and are thought to be linked to the decreased spatiotemporal correlations in the stress-drop behavior. •Link between complexity, multifractal, and stress-drop magnitude statistics.•Spatiotemporal dynamics of serrations is affected by strain rate and temperature.•Serrations exhibited the most complex behavior at a strain rate of 2 × 10-3 s-1.•Higher spatiotemporal correlations in the serrated flow at 500oC.